PENGARUH AUDIT TENURE PADA KECEPATAN PUBLIKASI LAPORAN KEUANGAN AUDITAN DENGAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI PEMODERASI - Anggreni, Ni Kadek Ayu Asri; Latrini, Made Yenni (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of audit tenure on speed publication of the audited financial statements, and whether the auditor industry specialization strengthen the influence of audit tenure on speed publication of audited financial statements. This study was performed on companies listed in the Indonesia Stock Exchange. Number of samples was 276 for 3( three) years. The sample in this study were taken by purposive sampling method. The analysis technique used is regression moderation / Moderated Regression Analysis (MRA). Based on the analysis found that the audit tenure positive effect on the speed of publication of the audited financial statements. This shows that the longer the tenure audit the financial statements audited publications speed manufacturing companies tend to rise or fast. Auditor industry specialization strengthens the positive effect of the audit tenure on speed publication of audited financial statements. It is proved that the longer the tenure of audit and reinforced by the auditor indusri specialty publications speed manufacturing companies audited financial statements or tends to rapidly increase.
Keywords: audit tenure, speed of publication, auditor industry specialization